STRESS STATUS AMONG THIRD-YEAR MEDICAL STUDENTS AT THAI NGUYEN UNIVERSITY OF MEDICINE AND PHARMACY AND ASSOCIATED FACTORS IN THE ACADEMIC YEAR 2024–2025 (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to describe the prevalence of stress and identify associated factors among third-year medical students at Thai Nguyen University of Medicine and Pharmacy in the academic year 2024–2025.Subject and method: A cross-sectional descriptive study was conducted among 423 third-year medical students from 4/2024 to 8/2025.Results: The prevalence of stress among participants was 61.9%, with 69.5% of stressed students experiencing moderate to extremely severe levels. Factors significantly associated with stress included: female gender (OR = 1.90; p = 0.002), rural background (OR = 1.71; p = 0.009), low household economic status (OR = 5.36; p < 0.001), history of academic repetition (OR = 7.85; p < 0.001), lack of close friendships (OR = 1.93; p = 0.007), dissatisfaction with clinical training (OR = 1.53; p = 0.043), dissatisfaction with clinical on-call schedules (OR = 1.78; p = 0.030), and having part-time jobs (OR = 1.59; p = 0.022).Conclusion: Stress is highly prevalent among third-year medical students and is influenced by a combination of individual, academic, and social factors. These findings highlight the urgent need for psychological support programs, adjustments in clinical training and scheduling, and early stress screening interventions to safeguard students’ mental health and academic performance.
Keywords: Stress, medical students, third year, DASS-21